RAQAMLI TA’LIM JARAYONINI SAMARALI TASHKIL ETISHDA GOOGLE CLASSROOM PLATFORMASIDAN FOYDALANISH - Ilyasova, Z.K. (SCIENCE and SOCIETY, 2024)
The article talks about the main advantages of using Google services, which enable the effective organization of the digital education process. Based on the analysis, the problems of creating a digital educational environment are identified, and recommendations are made for organizing the digital educational process through the Google Classroom platform.
Keywords: education; Digital Technology; Cloud Computing; Cloud Technology; Google Classroom; LMS; Google Drive; Google Docs; Google apps